Reconstruction of destroyed architectural monuments in Ukraine:: Between historical authenticity and modern needs of the urban environment - Chagovets, Olesya; Zhukova, Olena (Protection of Cultural Heritage, 2025)
In the context of the 60th anniversary of the Venice Charter, this report focuses on the challenges and opportunities for the reconstruction of destroyed monuments in Ukraine that go beyond traditional methods of restoration and conservation. The circumstances of extensive cultural heritage destruction due to hostilities in Ukraine have presented us with a crucial decision: how to preserve the historical identity and cultural memory of the nation? An example of this can be a city like Kharkiv, where the conservation of ruins or the creation of memorial sites proves to be impossible. This report analyses the challenges associated with the replication of monuments in the urban context of Ukraine, with a particular focus on ensuring the preservation of the urban environment and historical identity. Recognizing the loss of historic buildings as a threat, this report emphasizes the necessity of finding flexible solutions. Special attention is dedicated to preserving the authenticity of the destroyed objects while ensuring their adaptation to new functional needs and the demands of modern usage. Considering the uniqueness of each site, various approaches are explored, ranging from precise reconstruction to more interpretive methods that maintain the historical essence of the place while introducing new functional elements. The report outlines discussions on the moral and practical aspects of reconstructing destroyed objects, addressing the role of the Venice Charter in Ukraine today. It suggests updating doctrinal documents to tackle current urban challenges. The paper highlights the significance of ruined monuments for cities' historical and cultural identities, exemplifying cultural heritage preservation during wartime.